Infiltrated and Isostatic Laminated NCM and LTO Electrodes with Plastic Crystal Electrolyte Based on Succinonitrile for Lithium-Ion Solid State Batteries - Matthias Coeler; Vanessa van Laack; Frederieke Langer; Annegret Potthoff; Sören Höhn; Sebastian Reuber; Katharina Koscheck; Mareike Wolter (Batteries, 2021)
We report a new process technique for electrode manufacturing for all solid-state batteries. Porous electrodes are manufactured by a tape casting process and subsequently infiltrated by a plastic crystal polymer electrolyte (PCPE). With a following isostatic lamination process, the PCPE was further integrated deeply into the porous electrode layer, forming a composite electrode. The PCPE comprises the plastic crystal succinonitrile (SN), lithium conductive salt LiTFSI and polyacrylonitrile (PAN) and exhibits suitable thermal, rheological (ƞ = 0.6 Pa s @ 80 °C 1 s−1) and electrochemical properties (σ > 10−4 S/cm @ 45 °C). We detected a lowered porosity of infiltrated and laminated electrodes through Hg porosimetry, showing a reduction from 25.6% to 2.6% (NCM infiltrated to laminated) and 32.9% to 4.0% (LTO infiltrated to laminated). Infiltration of PCPE into the electrodes was further verified by FESEM images and EDS mapping of sulfur content of the conductive salt. Cycling tests of full cells with NCM and LTO electrodes with PCPE separator at 45 °C showed up to 165 mAh/g at 0.03C over 20 cycles, which is about 97% of the total usable LTO capacity with a coulomb efficiency of between 98 and 99%. Cycling tests at 0.1C showed a capacity of ~128 mAh/g after 40 cycles. The C-rate of 0.2C showed a mean capacity of 127 mAh/g. In summary, we could manufacture full cells using a plastic crystal polymer electrolyte suitable for NCM and LTO active material, which is easily to be integrated into porous electrodes and which is being able to be used in future cell concepts like bipolar stacked cells.